2001
DOI: 10.1161/01.hyp.37.2.774
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Hypercholesterolemia and Hypertension Augments Renal Function Abnormalities

Abstract: Abstract-Hypercholesterolemia and hypertension are both risk factors for end-stage renal disease. This study was designed to examine whether their coexistence augmented impairment in renal function and redox status. Regional renal hemodynamics and function in response to vasoactive challenges with acetylcholine or sodium nitroprusside were quantified by using electron-beam computed tomography in pigs after 12 weeks of either a normal (nϭ10) or hypercholesterolemic (nϭ10) diet, renovascular hypertension (nϭ7), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 37 publications
3
61
0
Order By: Relevance
“…We have previously shown in our model that a 12-week HC diet consistently did not increase blood pressure either. 8,17,25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown in our model that a 12-week HC diet consistently did not increase blood pressure either. 8,17,25 …”
Section: Resultsmentioning
confidence: 99%
“…6 -9 Of these, 7 ani-mals were fed for 10 weeks with the HC diet and then changed over to a normal pig chow for the remaining 6 weeks (HC-N; nϭ7), whereas in the other 7, the HC diet was sustained for the entire 16 weeks (HC-HC; nϭ7). We have previously shown that a 10-to 12-week HC diet in the swine resulted in endothelial dysfunction and activation of injurious mechanisms 8,17,18 in the absence of obstructive atherosclerotic plaques in different vascular beds (eg, aorta, renal, or coronary arteries), similar to humans with early atherosclerosis. 19 An additional group of pigs fed with a normal diet for 16 weeks was used as controls (normal; nϭ7).…”
Section: Methodsmentioning
confidence: 95%
“…The detrimental effect of protein intake observed in studies of patients with renal disease may also be related to the fact that many sources of animal protein are high in cholesterol and saturated fat. High cholesterol levels have also been shown to be a risk factor for progression of renal disease and may adversely affect renal function and renal hemodynamics (37)(38)(39). Therefore, since dietary intake of animal fat influences serum cholesterol level, we adjusted for animal fat intake as well as hypercholesterolemia.…”
Section: Discussionmentioning
confidence: 99%
“…Eight weeks before the imaging studies, unilateral renal artery stenosis (RAS) was induced. At baseline, under sterile conditions and fluoroscopic guidance, a metal wire coil was engaged in the proximal-middle section of the right renal artery as previously described (8,9,25,33). This induces a variable reactive hypertrophy of the arterial intimal wall, resulting in different degrees of hypertension.…”
Section: Methodsmentioning
confidence: 99%